Child-friendly justice and children's rights from criminal cases; Islamic Law notes - Purnamawati, Shinta Ayu; Aprilianda, Nurini; Endrawati, Lucky; Sulistiyo, Faizin (Faculty of Law, University of Muhammadiyah Malang, 2024)
This article aimed to discuss the Islamic law notes on child-friendly justice and the importance of protecting children's rights during the juvenile process. The reform of Juvenile Justice in Indonesia was based on the UN convention, where on January 26, 1990, in New York, the Indonesian Government signed the 1989 Convention on the Rights of Children. Thus, to protect children through criminal law, paying attention to the principles in the Convention on the Rights of the Child has been the norm. The Child Protection Law in Indonesia has regulated the age limit for a child who can be held accountable. The existence of provisions regarding the minimum age limit for children in the law is what is required by international documents, especially regarding the minimum age of criminal responsibility, namely at least 12 years. Such provisions are parallel to The Beijing Rules, which recommend an age limit that is not too low. The problem is the provision of the law that children under 12 years (meaning between 8-12 years) can still be processed for trial and can be subject to action. Even at the age of 8 years, it is still possible to process. The problem is whether the eight-year age limit needs to be higher. Even though they were not punished and were only subject to action, the experience during the process of being submitted to trial did not bring stigma and negative impacts for children of young age. Based on Islamic law notes, this article found that child-friendly justice